Influence of stochastic volatility for option pricing - Valaitytė, Akvilina; Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2004)
The article analyzes three models of stochastic volatility. Investigation of influence of stochastic volatility for pricing options traded in the Vilnius bank is done.